Integrating STEM-Oriented Inquiry-Based Learning to Improve Scientific Literacy and Problem-Solving Skills in Secondary Science Education - Firayani, Firayani (Scientica Education Journal, 2024)
This study aims to examine the effectiveness of STEM-oriented inquiry-based learning in improving students’ scientific literacy and problem-solving skills in secondary science education. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The participants consisted of two groups: an experimental group taught using STEM-oriented inquiry-based learning and a control group taught using conventional methods. Data were collected through a scientific literacy test and a problem-solving skills test. The results showed that the experimental group achieved significantly higher post-test scores compared to the control group. The normalized gain (N-gain) analysis indicated that the experimental group reached a medium to high level of improvement, while the control group remained in the low to medium category. Statistical testing using an independent sample t-test revealed a significant difference between the two groups (p < 0.05). Furthermore, STEM-oriented inquiry-based learning was found to enhance students’ abilities in problem identification, strategy development, and evaluation of solutions. These findings suggest that integrating STEM approaches with inquiry-based learning is an effective strategy to promote meaningful learning and develop essential 21st-century skills in science education.